(untitled) (Revista Científica Compendium, 2020)
The term governance includes, on the one hand, a system of rules that guide the actions of social actors and, on the other hand, the action of governing in an efficient and equitable way. Those aspects assume the existence of a society, whose problems must be solved, and they also have certain requirements which are advisable to satisfy, both by the State and diverse social institutions. In the search for solutions to the previous statement, changes, redesigns, and restructuring of governmental organizations have been encouraged in order to enable them to fulfill their primary role: to provide responses to the demands and needs of communities and their inhabitants. This diversity of actors implies the concretion of a concept related to governance, such as networking. In this context, the term electronic government (EG) arises, as a way to specifying mechanisms of interaction among both the State with citizens, employees, companies and intergovernmental bodies. Given these considerations, the present theoretical work, has as main objective to show some reflections upon the implications of the Governance in the EG, making emphasis on the actors involved and the relationships that are established among them.